THE ROLE OF LEARNING FACILITIES IN ENHANCING TOEFL TEST PREPARATION AMONG UNIVERSITY STUDENTS - Donny Adiatmana Ginting; Rosmen Rosmen; Muhammad Hassan; Fernando De Napoli Marpaung (PROJECT (Professional Journal of English Education), 2024)
The aim is to find the learning facilities' impact on students' preparation on the TOEFL test. Students must take the TOEFL test as one of the requirements for admission to universities, scholarships and job vacancies. The research approach is quantitative, and the research method is a survey. The population are ninety students from English Department Study Program, STKIP Al Maksum, who already took the TOEFL test; the sample were fifty-three students, and the author used random sampling to choose the sample. The data collection is from the questionnaire, which was analyzed through descriptive analysis as the data analysis technique. The result is that learning facilities consisting of large and comfortable classrooms, presentation equipment, books, computers and the internet influenced students' preparation for the TOEFL test. The average score was above 50% among the questions. Workshops and seminars also support students to build confidence and readiness in following the TOEFL test. In conclusion, adequate learning facilities can support students' preparation for taking the TOEFL test.